IMPROVEMENT OF PARTICULAR TIME EMPLOYMENT AGREEMENTS TO THE BPJS EMPLOYMENT PROGRAM AT PT TRIBARA INDO MARINATAMA - Muhammad Ilham Riowanto; Ninne Zahara Zahara (ConCEPt - Conference on Community Engagement Project, 2022)
Health is a primary human need that must be met to obtain prosperity. Unfortunately, many people do not have access to adequate health services in their area. This prompted the government to establish a National Social Security System in 2000. PT Tribara Indo Marinatama is a company located in Batam. However, in carrying out its operational activities, the company does not provide social security facilities to its employees. Because the company does not provide adequate BPJS for its employees, they cannot carry out their work safely and comfortably. This is the obligation of every company in Batam City. One of the obligations of employers is to guarantee occupational safety and health. Participation in the National Health Insurance Program is described in Presidential Regulation no. 12 of 2013 concerning Health Insurance, which was later revised in the explanation in Presidential Regulation Number 111 of 2013. As part of its obligations, employers must also participate in the National Health Insurance program. This program is carried out in stages starting January 1, 2014 until no later than January 1, 2019 to cover the entire population in Indonesia.